Colloid-Chemical Modification of Micellar Polyelectrolyte/Film-Forming Agents - Yu.V. Bolshak; Yu.F. Deinega; L.A. Sirota; T.A. Nesmeyanova; T.Yu. Ryabova (Adsorption Science & Technology, 1996)
The results of studies of the solubilization and adsorption stabilization of organic-diluted oligomers by aqueous polyelectrolyte/film-forming agents are presented. Experimental criteria for determining the stage at which the solubilization of modifiers changes to their adsorption stabilization are noted. The dependence of the conditions for emulsion modifier stabilization on the concentration of polyelectrolyte stabilizers has been determined. New compositions for electrodeposition, based on a combination of aqueous polyelectrolyte/film-forming agents with non-water-diluted oligomeric dispersions have been established. Polymer composite electrophoretic coatings with highly protective properties have been obtained.